Demographic characteristics and analysis of malocclusions of orthodontic patients seen at IIUM Dental Specialist Clinic, Kuantan, Pahang - Ismail, Khadilla; Ghazali@Suhaimi, Siti Sarah; Abu Bakar, Noraini; Mokhtar@Makhtar, Khairani Idah; Kharuddin, Azrul Fazwan (International Islamic University Malaysia, 2017)
Introduction: Malocclusion is one of the most common dental problems observed. Limited data is currently available regarding the demographics of malocclusion observed locally. Materials And Methods: This is a retrospective study where 770 patients were recruited from May 2009 till December 2014. 560 orthodontic study models that met the inclusion criteria were examined and the malocclusions were classified according to the British Standard Institute (BSI) incisor classification. Demographic pattern and their relationship were analysed by structural equation modelling using SPSS (version 23.0). Results: From 560 study models analysed, 72% were female. The age of the patients ranges from 7-12 years old (17.1%), 13-17 years old (55.9%) and >18 years old (27.0%). Majority of the patients were Malay followed by Chinese (5.7%), Indian (1.8%) and other races (1.8%) Treatments received were fixed appliances (FA) (60.0%), removable appliances (RA) (12.5%), functional appliances (FnA) (1.1%), combination of RA and FA (16.1%), combination of FnA and FA (2.1%) and consultation (8.2%). Types of malocclusions observed were Class I (25.7%), Class II/1(32.7%), Class II/2 (7.5%) and Class III (34.1%). There was significant association (p<0.05) between age and gender towards the types of malocclusions and treatments received were observed. Conclusion: Age and gender play significant role in determining the types of treatment received by patients with malocclusion. Data obtained will be beneficial for departmental future management and clinical planning. KEYWORDS: Demographics, Orthodontic, Malocclusion